1953
DOI: 10.1021/ie50521a054
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Titanium, Zirconium, and Stainless Steel in Organic Compounds

Abstract: ORGANICcompounds are not ordinarily thought of as being as destructive to metals as inorganic compounds such as the trong mineral acids and the heavy metal chlorides. Most organic acids are classified as weak acids, and their corrosive attack on the various common metals and alloys used in chemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1954
1954
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This study also demonstrated that corrosion of metallic oral piercings varies according to the nature of the surrounding medium, which is in line with previous literature on the corrosion of metallic alloys 24 . The two stronger inorganic acids were more corrosive than the two weaker inorganic acids, which is consistent with their higher chemical reactivity and their stronger dissociation as proton donors 25 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also demonstrated that corrosion of metallic oral piercings varies according to the nature of the surrounding medium, which is in line with previous literature on the corrosion of metallic alloys 24 . The two stronger inorganic acids were more corrosive than the two weaker inorganic acids, which is consistent with their higher chemical reactivity and their stronger dissociation as proton donors 25 …”
Section: Discussionsupporting
confidence: 92%
“…24 The two stronger inorganic acids were more corrosive than the two weaker inorganic acids, which is consistent with their higher chemical reactivity and their stronger dissociation as proton donors. 25 A range of different surface coatings, including spontaneously formed surface oxides, can act as passivation layers to protect the underlying metal. The passivation layer in stainless steel is chromium oxide, which forms on exposure to oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, titanium exhibits excellent corrosion resistance in organic acid solutions [3,7,67,68]. Aeration may be required to maintain passivity.…”
Section: General Corrosionmentioning
confidence: 99%
“…The corrosion rate in the latter medium increases with increasing temperature and acid concentration [67]. The corrosion resistance in oxalic acid can be improved by molybdenum alloying additions [72] or the addition of oxidizing agents such as antimony(III) [73].…”
Section: General Corrosionmentioning
confidence: 99%
“…Especially interesting is the metal's resistance to moist chlorine gas (1), sodium and calcium hypochlorites, chloride salt solutions including cupric and ferric chlorides, and some mixed acids (1,2). Titanium also has a high resistance to many organic acids and compounds (1,6), but the metal is attacked by hydrochloric, hydrofluoric, sulfuric, oxalic, trichloroacetic, and unaerated formic acid solutions.…”
Section: Introductionmentioning
confidence: 99%